Analysis of Volunteer interest and work motivation Islamic philanthropy institutions reviewed from theory cognitive evaluation: Study at Baznas Bandar Lampung City - Kurniati, Erlin; Utamie, Zathu Restie; Aulia, Nanda (Journal of Management and Digital Business, 2024)
Islamic philanthropic institutions are essential in the humanitarian sector, especially in distributing ZIS (zakat, infaq, and sadaqah). Institutions need to increase the interest and motivation of volunteers so they can work optimally. The main objective of this research is to measure the interest and work motivation of Bandar Lampung City BAZNAS volunteers and to understand the extent of extrinsic motivation support provided by Bandar Lampung City BAZNAS to its volunteers through the lens of cognitive evaluation theory. The research method used in this research is quantitative descriptive research, with the number of respondents being 20 BAZNAS volunteers from Bandar Lampung. The research results show that BAZNAS volunteers want to continue their involvement with BAZNAS and contribute to its mission for a long time. After joining BAZNAS Bandar Lampung City as volunteers, they received many benefits, including developing skills and expertise. BAZNAS Bandar Lampung City provides opportunities for volunteers to participate in various activities and, as much as possible, create a good and conducive work environment between interest, motivation, and support by cognitive evaluation theory.